A Clinical Study of Kerosene Poisoning Among Children in a Rural Medical College Hospital - Mohammed Anees Ur Rahman; Mohammed Nayaz Ahmed; Ananda Kumar T S; Kumar G V (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: Acute poisoning in children adversely impacts on global child health and the patterns and morbidity of poisoning vary across different geographic regions due to variable cultural, social, economic, and geographic factors.Kerosene Poisoning is an important and preventable cause of morbidity and mortality in the developing world. Kerosene is a hydrocarbon product of petroleum distillate, made up of paraffin and naphthalenes. Subjects & Methods: The complications of kerosene poisoning include hypoxia, pneumonitis, bacterial pneumonia, pneumatocele, pleural effusion, pneumothorax, subcutaneous emphysema and empyema. The usual gastrointestinal symptoms of kerosene poisoning are abdominal pain, vomiting and diarrhoea. Its Central Nervous System manifestations include drowsiness and convulsions. Results:Out of 22 children with kerosene poisoning 18 (81.81%) were male and 4 (18.18%) were female. There was only one case (4.54%) of kerosene poisoning with less than one year, between 1-5 years there were 19 (86.36%) cases and above 6 years there were 2 (9.09%) cases of kerosene poisoning.There were 11(50%) cases were seen during summer followed by 6 (27.27%) cases seen in monsoon and there were 5 (22.72%) cases in winter season.Toddler age, children from rural area, summer season was found major risk factors in our study for kerosene ingestion and is mostly due to improper storage of kerosene.Respiratory complaints like cough and dyspnoea are the two most common symptoms in kerosene poisoning. Conclusion:There is a need to create public awareness regarding kerosene oil storage and accessibility at home from the younger children.